Composition, supporting layer and display module
By using compositions that use acrylic polymers and hydroxide polymers in the supporting layer of the flexible OLED screen, reduce the dielectric constant to shield the static electricity, solve the problem of green and shiny screens caused by static accumulation, significantly improved improvement, significantly improved The display effect and product yield.
Patent Information
- Application Number
- CN202411399941.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-21
AI Technical Summary
During use, the accumulation and discharge of static electricity in the flexible OLED screen will cause the screen to turn green and shiny, affecting the display effect.
A specific composition, which includes acrylic polymers and a hydroxide polymer with a total mass of 5-10%, is used to prepare the support layer, reducing the dielectric constant to shield static electricity.
It effectively prevents static electricity from entering the screen body, reduces the electrical damage caused by static electricity to thin film transistors, improves the display effect of the display module, reduces the occurrence of green and shiny screen bodies, and improves the production yield.
Smart Images

Figure CN119331373A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of display technology, and in particular relates to a composition, a supporting layer and a display module. Background Art
[0002] With the development of display technology, people have put forward higher requirements on the performance of display devices. Among them, flexible OLED screens have the characteristics of being able to be bent at will, which gives them excellent visual enjoyment when unfolded, and the advantage of being portable and small in size when stored. Therefore, they have gradually become a major trend in the development of electronic products.
[0003] However, during the use of the flexible OLED screen, the accumulation of static electricity and its discharge process will cause damage to the display screen to varying degrees, seriously affecting the normal display function of the display screen. The most prominent problem is the phenomenon of the screen turning green and shiny due to static electricity accumulation. Summary of the invention
[0004] In view of the above problems existing in the prior art, the present invention provides a composition, the specific composition of which has a lower dielectric constant, so that it can be used as a medium for effectively shielding static electricity to overcome the related defects caused by static electricity.
[0005] The invention provides a support layer, the raw material of which includes the above composition, so the dielectric constant of the support layer is low, the antistatic property is improved, and the support layer has the function of preventing static electricity injection.
[0006] The present invention also provides a display module, which includes the above-mentioned support layer, so that the display module can effectively prevent static electricity from entering the screen body, thereby avoiding the occurrence of the green and shiny screen body due to static electricity accumulation.
[0007] The purpose of the present invention is specifically achieved through the following technical solutions:
[0008] The first aspect of the present invention provides a composition comprising an acrylic polymer and a fluorinated polymer accounting for 5-10% of the total mass of the acrylic polymer; the fluorinated polymer comprises at least one hydroxyl-terminated fluorinated polymer.
[0009] Further, the fluorinated polymer includes at least one of hydroxyl-terminated polyvinylidene fluoride (PVDF), hydroxyl-terminated polytetrafluoroethylene (PTEF), hydroxyl-terminated tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer (PFA), hydroxyl-terminated fluorinated ethylene propylene copolymer (FEP), hydroxyl-terminated polychlorotrifluoroethylene (PCTFE), hydroxyl-terminated tetrafluoroethylene-chlorotrifluoroethylene copolymer, and hydroxyl-terminated ethylene-chlorotrifluoroethylene copolymer.
[0010] Furthermore, the hydroxyl value of the fluorinated polymer is 0.5 to 4.5.
[0011] Furthermore, the molecular weight of the fluorinated polymer is 1,000 to 50,000.
[0012] Furthermore, the dielectric constant of the fluorinated polymer is 1-3.
[0013] Furthermore, the composition also includes an active diluent and an auxiliary agent.
[0014] Furthermore, the acrylic polymer includes a homopolymer or a copolymer formed by at least one monomer selected from the group consisting of (meth)acrylic acid, polyurethane (meth)acrylic acid, polyester (meth)acrylic acid, polyether (meth)acrylic acid, and epoxy (meth)acrylic acid.
[0015] Furthermore, the storage modulus of the composition at 25° C. is 100 to 300 kPa, and the storage modulus at 200° C. is 1 to 200 kPa.
[0016] Furthermore, the adhesion of the composition is 600 to 3000 g.
[0017] Furthermore, the dielectric constant of the composition is 2.5-5.
[0018] The second aspect of the present invention provides a support layer, which comprises a release film layer, a functional layer and a protective film layer in sequence; the functional layer comprises the composition described in the first aspect of the present invention.
[0019] Furthermore, the transmittance of the functional layer is 70-100%.
[0020] Furthermore, the haze of the functional layer is 0-10.
[0021] A third aspect of the present invention provides a display module, comprising a display panel and the supporting layer according to the second aspect of the present invention located on a non-light emitting side of the display panel.
[0022] The composition provided by the present invention has the following beneficial effects:
[0023] The composition provided by the present invention has a specific composition and can exhibit a lower dielectric constant, so it has a relatively excellent shielding effect on static charges, can significantly improve the antistatic performance of the composition, and is beneficial to reducing the accumulation of static charges on the screen, thereby improving the display effect of the display module by inhibiting the damage caused by static charges to the electrical properties of the thin-film transistor, effectively reducing the probability of the display module appearing green and shiny, and improving the production yield of the display module.
[0024] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Shown is a schematic structural diagram of a support layer provided by an embodiment of the present invention;
[0026] Description of reference numerals:
[0027] Release film layer-1, composition layer-2, substrate layer-3, protective film layer-4. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0030] In the application or testing process of the display module, a copper rod is generally used to rub the whole machine or module to characterize its antistatic performance. The above operation will inject a large amount of static charge into the display module. Some of the static charge will directly enter the display panel along the edge of the supporting layer that supports and protects the back of the display module, and affect the electrical performance of the thin film transistor TFT of the display panel in the display module through the back channel effect, thereby causing the display panel to display abnormally, especially the screen body to glow green. On this basis, at present, rubber resin materials are often added to the supporting layer rubber material to reduce its dielectric properties, thereby improving the overall antistatic performance of the display module. However, rubber resin materials are difficult to cross-link under normal conditions, and only a very small number of groups can be copolymerized with the main agent of the support layer rubber material. This leads to limited room for improving the cross-linking density of the internal structure of the entire support layer rubber material, and the phenomenon of two-phase separation may also occur, thereby affecting the viscosity and optical properties of the support layer rubber material. More importantly, the dielectric constant of rubber resin materials is generally around 2.5-3, and the optimization of the dielectric constant characteristics of the support layer rubber material is not obvious enough, and the added content is also difficult to control.
[0031] In order to solve the above problems, the first aspect of the present invention provides a composition, the specific composition of which has a lower dielectric constant, so that it can be used as a medium for effectively shielding static electricity to overcome the related defects caused by static electricity. The details are as follows:
[0032] A composition comprises an acrylic polymer and a fluorinated polymer accounting for 5-10% of the total mass of the acrylic polymer; the fluorinated polymer comprises at least one terminal hydroxyl fluorinated polymer.
[0033] Fluorinated polymers, because they contain fluorine atoms and hydrogen atoms in their molecular structure, have high polarizability and thus excellent dielectric properties. Moreover, fluorinated polymers generally have good chemical resistance, processability, fatigue resistance and creep resistance, which helps to improve the stability of excellent dielectric properties. Therefore, the present invention can make the composition exhibit a lower dielectric constant by adding an appropriate amount of fluorinated polymer to a composition having an acrylic polymer, so that it can obtain a relatively excellent shielding effect on static charge, significantly improve the antistatic performance of the composition, and help reduce the accumulation of static charge on the screen body, thereby improving the display effect of the display module by suppressing the damage caused by static charge to the electrical properties of the thin film transistor, effectively reducing the probability of the display module appearing green and shiny, and improving the production yield of the display module.
[0034] Further, the fluorinated polymer includes at least one hydroxyl-terminated fluorinated polymer. When the fluorinated polymer added to the composition having an acrylic polymer contains a terminal hydroxyl group, the fluorinated polymer can react with groups such as -NCO and -COOH in the acrylic polymer through the terminal hydroxyl group as a grafting group, and connect the fluorinated polymer as a side chain to the segment structure of the composition, thereby adjusting and improving the internal structure of the acrylic polymer, adjusting the dielectric constant of the acrylic polymer at the source, and improving its antistatic performance. In addition, the effect of adjusting the dielectric constant of the composition by adding a fluorinated polymer containing a terminal hydroxyl group is better. The amount of fluorinated polymer to be added does not need to be too much, and it can be controlled within a suitable range. In a specific embodiment, the amount of fluorinated polymer added accounts for 5-10% of the total mass of the acrylic polymer in the composition; specifically, the amount of fluorinated polymer added can be 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%; in a preferred embodiment, the amount of fluorinated polymer added accounts for 5.5-7% of the total mass of the acrylic polymer in the composition.
[0035] Furthermore, when the fluorinated polymer added to the composition having an acrylic polymer contains a terminal hydroxyl group, the fluorinated polymer containing the terminal hydroxyl group and the acrylic polymer can further form a cross-linked structure through the reaction of the grafted group, thereby improving the cross-linking density of the entire composition system, thereby avoiding a sharp decrease in the viscosity of the composition system due to the addition of the fluorinated polymer and reducing the impact on the optical properties of the composition (for example: transmittance, haze, etc.).
[0036] Therefore, the above solution of the present invention can achieve better effect than the prior art. In order to further improve the effect, one or more of the following solutions can be further defined.
[0037] In a specific embodiment, the fluorinated polymer includes at least one of hydroxyl-terminated polyvinylidene fluoride (PVDF), hydroxyl-terminated polytetrafluoroethylene (PTEF), hydroxyl-terminated tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer (PFA), hydroxyl-terminated fluorinated ethylene propylene copolymer (FEP), hydroxyl-terminated polychlorotrifluoroethylene (PCTFE), hydroxyl-terminated tetrafluoroethylene-chlorotrifluoroethylene copolymer, and hydroxyl-terminated ethylene-chlorotrifluoroethylene copolymer. In a preferred embodiment, the fluorinated polymer includes at least one of hydroxyl-terminated polyvinylidene fluoride and hydroxyl-terminated fluorinated ethylene propylene copolymer.
[0038] In order to improve the dielectric properties of the composition, in a specific embodiment, the hydroxyl value of the fluorinated polymer is 0.5 to 4.5. Specifically, the hydroxyl value of the fluorinated polymer can be 0.5, 1.5, 2.5, 3.5, or 4.5. Among them, the hydroxyl value is used to characterize the content of hydroxyl groups in the fluorinated polymer. By limiting the hydroxyl value in the fluorinated polymer as described above, the hydroxyl content in the fluorinated polymer can be further controlled, thereby adjusting the degree of reaction between the terminal hydroxyl groups of the fluorinated polymer and the -NCO, -COOH and other groups in the acrylic polymer, thereby further rationally regulating the dielectric constant of the acrylic polymer and improving the antistatic properties of the composition. In a preferred embodiment, the hydroxyl value of the fluorinated polymer is 1.6 to 3.
[0039] Furthermore, when the molecular weight of the fluorinated polymer is 1000 to 50000, the dielectric constant of the composition will be further reduced, which is more conducive to shielding static charge. Specifically, the molecular weight of the fluorinated polymer can be 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000, 20000, 30000, 40000, 50000. When the molecular weight of the fluorinated polymer is too large, the viscosity of the reaction system will be too large and the processability will be poor. When the molecular weight of the fluorinated polymer is too small, it will easily cause the problem of small molecule precipitation under high temperature conditions. Therefore, the benefit of the static charge shielding effect can be increased by controlling the molecular weight of the fluorinated polymer. In a preferred embodiment, the molecular weight of the fluorinated polymer is 4000 to 8000.
[0040] Moreover, in order to further control the effect of the fluorinated polymer on the dielectric constant of the composition, in a specific embodiment, the dielectric constant of the fluorinated polymer can be controlled within the range of 1 to 3. Specifically, the dielectric constant of the fluorinated polymer can be 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3. In a preferred embodiment, the dielectric constant of the fluorinated polymer is 1.2 to 2.
[0041] In a specific embodiment, the acrylic polymer includes a homopolymer or copolymer formed by at least one monomer selected from the group consisting of (meth)acrylic acid, polyurethane (meth)acrylic acid, polyester (meth)acrylic acid, polyether (meth)acrylic acid, and epoxy (meth)acrylic acid.
[0042] In one specific embodiment, the composition further comprises a reactive diluent and an auxiliary agent.
[0043] The reactive diluent includes a (meth)acrylate polymer, for example, a homopolymer or copolymer formed by at least one monomer selected from ethyl (meth)acrylate, butyl (meth)acrylate, methyl (meth)acrylate, hydroxy (meth)acrylate, glycol ethyl (meth)acrylate, glycol butyl (meth)acrylate, glycol methyl (meth)acrylate, glycol hydroxy (meth)acrylate, alkoxy ethyl (meth)acrylate, alkoxy butyl (meth)acrylate, alkoxy methyl (meth)acrylate, and hydroxy (alkoxymethyl)acrylate.
[0044] The additives include one or more of a defoamer, a leveling agent, an inhibitor, and an initiator.
[0045] The main function of the defoamer is to inhibit, reduce and eliminate bubbles in the composition. As long as the defoamer can meet the above performance requirements, the application does not specifically limit the selection of the defoamer, such as alcohol compounds.
[0046] The role of the polymerization inhibitor is mainly to improve the storage stability of the composition. The polymerization inhibitor may include at least one of hydroquinone, benzoquinone, p-hydroxyanisole, 2-tert-butylhydroquinone, 2,5-di-tert-butylhydroquinone, tris(N-nitroso-N-phenylhydroxylamine)aluminum salt (inhibitor 510), etc.
[0047] The leveling agent is mainly used to improve the fluidity of the composition and the wetting performance on the substrate. As long as the leveling agent can meet the above performance requirements, the application does not make any specific restrictions on the selection of the leveling agent, such as silicone resins.
[0048] The initiator is mainly used to initiate the polymerization reaction of the composition to further reduce the dielectric constant. The initiator may include, for example, a photoinitiator, which includes one or more of 1-hydroxycyclohexyl phenyl ketone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, 1-hydroxycyclohexyl phenyl ketone, 2-benzyl-2-dimethyl-1-(4-morpholinophenyl)butanone, benzophenone, 4-phenylbenzophenone, benzoin diethyl ether, 2-chlorothioxanthone, and 2,4-diethylthioxanthone.
[0049] Further, the amount of reactive diluent added accounts for 40-80% of the total mass of acrylic polymer, and the total amount of various auxiliary agents added accounts for 0-10% of the total mass of acrylic polymer. The present invention combines components with different polarities in a certain proportion, and finally makes the composition show a lower dielectric constant, so the composition can act in a scene with a demand for preventing static electricity inhalation to effectively shield static electricity. The present application does not limit the specific application mode of the composition, which can be used alone or mixed with other functional components as an antistatic functional component. When mixed with other functional components, it is preferred to first mix the acrylic polymer, fluorinated polymer, reactive diluent and auxiliary agent in a defined mass ratio to obtain a composition, and then the composition is mixed with other functional components in the next step. In a preferred embodiment, the amount of reactive diluent added accounts for 50-70% of the total mass of acrylic polymer, and the total amount of various auxiliary agents added accounts for 2-7% of the total mass of acrylic polymer.
[0050] In addition, the present application also has no particular limitation on the order of adding the components constituting the composition, as long as the components can be mixed evenly.
[0051] Further, the dielectric constant of the composition of the present invention is 2.5 to 5. Specifically, the dielectric constant of the composition can be 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5. By limiting the dielectric constant of the composition as above, the electrostatic shielding performance of the composition can be further improved. In a preferred embodiment, the dielectric constant of the composition is 2.2 to 2.7.
[0052] In addition, by further controlling the composition of the composition, its storage modulus and adhesion can be improved to avoid affecting various aspects of the performance of the functional layer due to the addition of fluorinated polymers in the composition. In a specific embodiment, the storage modulus of the composition at 25°C is 100-300 kPa, and the storage modulus at 200°C is 1-200 kPa. Specifically, the storage modulus of the composition at 25°C can be 100 kPa, 110 kPa, 120 kPa, 130 kPa, 140 kPa, 150 kPa, 160 kPa, 170 kPa, 180 kPa, 190 kPa, 200 kPa, 210 kPa, 220 kPa, 230 kPa, 240 kPa, 250 kPa, 260 kPa, 270 kPa, 280 kPa, 290 kPa, a, 300kPa; the storage modulus of the composition at 200°C can be 1kPa, 10kPa, 20kPa, 30kPa, 40kPa, 50kPa, 60kPa, 70kPa, 80, 90kPa, 100kPa, 110kPa, 120kPa, 130kPa, 140kPa, 150kPa, 160kPa, 170kPa, 180kPa, 190kPa, 200kPa. In a preferred embodiment, the storage modulus of the composition at 25°C is 150kPa to 270kPa, and the storage modulus at 200°C is 10kPa to 100kPa.
[0053] In a specific embodiment, the adhesion of the composition is 600 to 3000 g. Specifically, the adhesion of the composition can be 600 g, 700 g, 800 g, 900 g, 1000 g, 1100 g, 1200 g, 1300 g, 1400 g, 1500 g, 1600 g, 1700 g, 1800 g, 1900 g, 2000 g, 2100 g, 2200 g, 2300 g, 2400 g, 2500 g, 2600 g, 2700 g, 2800 g, 2900 g, 3000 g. In a preferred embodiment, the adhesion of the composition is 1000 g to 2500 g.
[0054] The second aspect of the present invention provides a support layer. In a specific embodiment, Figure 1 As shown, the support layer includes a release film layer 1, a composition layer 2, a substrate layer 3 and a protective film layer 4 in sequence; wherein the composition layer 2 and the substrate layer 3 together constitute the functional layer, and the functional layer includes the composition described in the first aspect of the present invention. The functional layer of the support layer includes the above-mentioned composition, so the dielectric constant of the support layer will also be maintained at a low level, and its antistatic performance is effectively improved, which has the effect of preventing static injection. However, it can be understood that in addition to the composition, the functional layer can also include other components.
[0055] In a specific embodiment, the transmittance of the functional layer is 70-100%. Specifically, the transmittance of the functional layer can be 70%, 75%, 80%, 85%, 90%, 95%, 100%. In a preferred embodiment, the transmittance of the functional layer is 80-95%.
[0056] In a specific embodiment, the haze of the functional layer is 0 to 10. Specifically, the haze of the functional layer can be 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10. In a preferred embodiment, the haze of the functional layer is 0 to 4.
[0057] In a specific embodiment, the thickness of the release film layer is 25 to 75 μm, the thickness of the composition layer is 5 to 50 μm, the thickness of the substrate layer is 30 to 100 μm, and the thickness of the protective film layer is 25 to 75 μm.
[0058] In addition to the above-mentioned function of shielding static electricity, the functional layer mainly plays a role in ensuring the bonding effect of the support layer.
[0059] Since the fluorinated polymer added in the present invention contains terminal hydroxyl groups, when other components are added to the composition having an acrylic polymer, the fluorinated polymer containing terminal hydroxyl groups and the acrylic polymer can further form a crosslinked structure through the reaction of the grafted groups, thereby improving the crosslinking density of the entire composition system, thereby avoiding a sharp decrease in the modulus and viscosity of the composition system due to the addition of the fluorinated polymer, thereby avoiding a decrease in the mechanical properties of the functional layer such as the storage modulus and adhesion, and the crosslinking of the composition system also reduces the influence on the optical properties of the composition (for example: transmittance, haze, etc.), thereby ensuring that the functional layer also has excellent optical properties.
[0060] The third aspect of the present invention provides a display module, comprising a display panel and the support layer described in the second aspect of the present invention located on the non-light-emitting side of the display panel. The display module comprises the support layer, so the display module can effectively prevent static electricity from entering the screen body, thereby avoiding the occurrence of the green and shiny screen body caused by static electricity.
[0061] Furthermore, the display panel has a light-emitting side and a non-light-emitting side that are arranged relatively to each other, and the support layer arranged on the non-light-emitting side is mainly used to support and protect the display panel, so as to effectively buffer the external impact force received by the display module during the application process. In a specific embodiment, a protective film is arranged on a side of the support layer away from the display panel, and the protective film can protect the display module in the operation process, and can be torn off when protection is not needed.
[0062] In the application or detection process of the display module, a copper rod is generally used to rub the whole machine or module to characterize its antistatic performance. The operation will inject a large amount of static charge into the display module, and part of the static charge will directly enter the display panel along the support layer that plays a supporting and protective role on the back of the display module, and affect the electrical properties of the thin film transistor TFT of the display panel in the display module through the back channel effect, thereby causing the display panel to display abnormally, especially the screen body to glow green. The present invention arranges the above-mentioned support layer on the non-light-emitting side of the display panel, and arranges a functional layer with the above-mentioned composition as a raw material in the support layer, which can act as an electrostatic barrier to prevent the classic and pass through the support layer to enter the display panel, thereby improving the display effect of the display panel by avoiding damage to the electrical properties of the thin film transistor TFT, and improving the product yield of the display module.
[0063] The present invention does not limit the specific composition of the display panel. Generally, it includes a screen body and a substrate that are stacked, and the support layer is located on one side of the substrate. The present invention does not limit the display type of the screen body. For example, it can be an OLED display screen that includes at least a cathode layer, a light-emitting layer, and an anode layer. The substrate is located on the non-light-emitting side of the screen body and is mainly used to protect the screen body to prevent the screen body from being damaged during operation or use. The substrate is generally made of a flexible material, such as polyimide.
[0064] In addition, on the light-emitting side of the display panel, there are stacked polarizers, optical adhesive layers, and cover plates in the order of gradually moving away from the display panel. The polarizer is used to adjust the light emitted by the display panel to improve the display quality; the cover plate is used to seal and protect the display template to prevent it from being damaged by the outside world; the optical adhesive layer is light-transmissive and is used to fix and bond the cover plate and the polarizer.
[0065] The present invention does not impose any particular limitation on the thickness of each film layer constituting the display module. Specifically, the thickness of the screen body, substrate, support layer, cover plate, polarizer and each adhesive layer is consistent with the existing thickness in the art.
[0066] Since the display module of the present invention has excellent display effects, electronic devices including the display module of the present invention (including but not limited to mobile phones, televisions, computers, etc.) also have excellent display effects, and can greatly reduce the occurrence of green screen phenomena caused by electrostatic adsorption during application.
[0067] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0068] In the following examples and comparative examples, all the reaction raw materials used can be obtained by commercial purchase or conventional methods, which will not be described in detail here.
[0069] Example 1a
[0070] Preparation of the composition:
[0071] After proper amounts of methacrylic acid and ethyl acrylate are mixed, a photoinitiator 1-hydroxycyclohexyl phenyl ketone is added, and then a proper amount of terminal hydroxyl polyvinylidene fluoride is added, and then the system after adding the initiator is subjected to UV irradiation. After the system is cured, the composition is obtained, in which the content of terminal hydroxyl polyvinylidene fluoride accounts for 7% of the total mass of polymethacrylic acid, and the molecular weight of terminal hydroxyl polyvinylidene fluoride is 6000.
[0072] Example 2a
[0073] The preparation method of the composition of this embodiment is basically the same as that of embodiment 1a, except that the content of the terminal hydroxyl group polyvinylidene fluoride accounts for 6% of the total mass of the polymethacrylic acid.
[0074] Example 3a
[0075] The preparation method of the composition of this embodiment is basically the same as that of embodiment 1a, except that the content of the terminal hydroxyl group polyvinylidene fluoride accounts for 9% of the total mass of the polymethacrylic acid.
[0076] Example 4a
[0077] The preparation method of the composition of this embodiment is basically the same as that of embodiment 1a, except that the content of the terminal hydroxyl group polyvinylidene fluoride accounts for 5% of the total mass of the polymethacrylic acid.
[0078] Example 5a
[0079] The preparation method of the composition of this embodiment is basically the same as that of embodiment 1a, except that the added fluorinated polymer is changed to a fluorinated ethylene-propylene copolymer having terminal hydroxyl groups.
[0080] Example 6a
[0081] The preparation method of the composition of this embodiment is basically the same as that of embodiment 1a, except that the added fluorinated polymer is hydroxyl-terminated polytetrafluoroethylene.
[0082] Example 7a
[0083] The preparation method of the composition of this embodiment is basically the same as that of embodiment 1a, except that the molecular weight of the hydroxyl-terminated polyvinylidene fluoride is 2000.
[0084] Example 8a
[0085] The preparation method of the composition of this embodiment is basically the same as that of embodiment 1a, except that the molecular weight of the hydroxyl-terminated polyvinylidene fluoride is 10,000.
[0086] Comparative Example 1a
[0087] The preparation method of the composition of this comparative example is basically the same as that of Example 1a, except that the content of the terminal hydroxyl group polyvinylidene fluoride accounts for 15% of the total mass of the polymethacrylic acid.
[0088] Comparative Example 2a
[0089] The preparation method of the composition of this comparative example is basically the same as that of Example 1a, except that the content of the terminal hydroxyl group polyvinylidene fluoride accounts for 3% of the total mass of the polymethacrylic acid.
[0090] Comparative Example 3a
[0091] The preparation method of the composition of this comparative example is basically the same as that of Example 1a, except that the added fluorinated polymer is non-hydroxyl-terminated polyvinylidene fluoride.
[0092] Comparative Example 4a
[0093] The preparation method of the composition of this comparative example is basically the same as that of Example 1a, except that no fluorinated polymer is added.
[0094] The system after adding the initiator in the above-mentioned embodiments 1a-8a and comparative examples 1a-2a is coated on the surface of a PET substrate and irradiated with UV light to obtain a functional layer including the composition of the above-mentioned embodiments 1a-8a and comparative examples 1a-4a. The functional layer is named as embodiments 1b-8b and comparative examples 1b-4b, respectively.
[0095] Test Case
[0096] 1. Dielectric constant test
[0097] The dielectric constants of the fluorinated polymers used in the compositions of Examples 1a to 8a and Comparative Examples 1a to 3a, and the compositions of Examples 1a to 8a and Comparative Examples 1a to 4a were tested using an LCR tester. The specific results are shown in Table 1.
[0098] 2. Hydroxyl value test
[0099] After dissolving the fluorinated polymer used in the compositions of some Examples 1a to 8a and Comparative Examples 1a to 3a with ethanol, 5 mL of anhydrous pyridine solution of phthalic anhydride (42 g of phthalic anhydride dissolved in 300 mL of anhydrous pyridine) and phenolphthalein indicator were added to each gram of the fluorinated polymer to obtain a sample to be tested. The sample to be tested was titrated with a potassium hydroxide solution. The titration was stopped when the color of the sample turned light pink and the color did not disappear after shaking. The volume of the potassium hydroxide solution consumed was recorded. The hydroxyl content in the composition to be tested was calculated based on the amount of phthalic anhydride and potassium hydroxide used, and expressed as a hydroxyl value (the hydroxyl value represents the mass of KOH in the fluorinated polymer used in 100 g of the composition that is equimolar to the hydroxyl group, mg). The results are shown in Table 2.
[0100] 4. Storage modulus and adhesion test
[0101] 1) Take some of the compositions of Examples 1a to 8a and Comparative Examples 1a to 4a and stack them into 1 mm samples, and use DMA (dynamic mechanical analyzer) in rotation mode to measure their storage modulus. The results are shown in Table 3.
[0102] 2) The adhesion of the compositions in Examples 1a to 8a and Comparative Examples 1a to 4a was tested with reference to the ASTM D3330 test standard. The results are shown in Table 3.
[0103] 5. Transmittance and haze test
[0104] 1) In a standard laboratory environment, a spectrophotometer was used to test. The functional layers of some embodiments 1b to 8b and comparative examples 1b to 4b were placed in the corresponding test holes of the test equipment as test materials and fixed. The light source of the equipment was required to be incident from the adhesive surface for testing. The results are shown in Table 3.
[0105] 2) In a standard laboratory environment, a haze colorimeter was used to test, and some functional layers of Examples 1b to 8b and Comparative Examples 1b to 4b were placed in the corresponding test holes of the test equipment as test materials and fixed, and the light source of the equipment was required to be incident from the adhesive surface for testing. The results are shown in Table 3.
[0106] 6. Copper rod friction test
[0107] The functional layers of test examples 1b to 8b and comparative examples 1b to 4b were made into support layers. The preparation method of the support layers is as follows: a release film layer of 45 μm / functional layer (composition layer of 15 μm / PET layer of 60 μm) / protective film layer of 50 μm was stacked in sequence to obtain a support layer; the support layer was then set on the light-emitting side of the display panel to obtain different display modules, and then the brightness and chromaticity data of each display module at different grayscales were tested. Subsequently, the display module was fixed on a copper rod scribing stage, the friction pressure was set to 1 N, the friction speed was set to 100 mm / s, and the copper rod scribing equipment was operated. The brightness and chromaticity data were tested 24 hours after scribing.
[0108] If the chromaticity difference and brightness difference before and after the copper rod is rubbed are both less than 0.05, and the edge of the screen does not appear green when the display module is lit, the test is passed; if at least one of the chromaticity difference and brightness difference before and after the copper rod is rubbed is greater than 0.05, or the edge of the screen appears green when the display module is lit, the test is not passed. The results are shown in Table 4.
[0109] Table 1
[0110]
[0111]
[0112] Table 2
[0113] Group Hydroxyl value Example 1a 3.0 Example 2a 2.8 Example 3a 4.0 Example 4a 2.0 Example 5a 1.0 Example 6a 0.8 Example 7a 2.3 Example 8a 0.5 Comparative Example 1a 5 Comparative Example 2a 0.3 Comparative Example 3a 0.05
[0114] Table 3
[0115]
[0116]
[0117] Table 4
[0118] Group Is the edge of the screen green? Test passed Example 1b no OK Example 2b no OK Example 3b no OK Example 4b no OK Example 5b no OK Example 6b no OK Example 7b no OK Example 8b no OK Comparative Example 1b yes NG Comparative Example 2b yes NG Comparative Example 3b yes NG Comparative Example 4b yes NG
[0119] It can be seen from Table 1 and Table 2 that the composition of the embodiment of the present invention has a lower dielectric constant, especially when a fluorinated polymer with terminal hydroxyl groups is added to the composition, the performance of suppressing the green screen phenomenon of the display module is more outstanding.
[0120] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A composition, characterized in that The invention comprises an acrylic polymer and a fluorinated polymer accounting for 5-10% of the total mass of the acrylic polymer; the fluorinated polymer comprises at least one fluorinated polymer with terminal hydroxyl groups.
2. The composition according to claim 1, characterized in that The fluorinated polymer comprises at least one of hydroxyl-terminated polyvinylidene fluoride (PVDF), hydroxyl-terminated polytetrafluoroethylene (PTEF), hydroxyl-terminated tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer (PFA), hydroxyl-terminated fluorinated ethylene propylene copolymer (FEP), hydroxyl-terminated polychlorotrifluoroethylene (PCTFE), hydroxyl-terminated tetrafluoroethylene-chlorotrifluoroethylene copolymer, and hydroxyl-terminated ethylene-chlorotrifluoroethylene copolymer; Preferably, the hydroxyl value of the fluorinated polymer is 0.5 to 4.
5.
3. The composition according to claim 1, characterized in that The molecular weight of the fluorinated polymer is 1000 to 50000; And / or, the dielectric constant of the fluorinated polymer is 1-3.
4. The composition according to claim 1, characterized in that The composition also includes a reactive diluent and an adjuvant; Preferably, the acrylic polymer includes a homopolymer or a copolymer formed from at least one monomer selected from the group consisting of (meth)acrylic acid, polyurethane (meth)acrylic acid, polyester (meth)acrylic acid, polyether (meth)acrylic acid, and epoxy (meth)acrylic acid.
5. The composition according to claim 1, characterized in that The storage modulus of the composition at 25° C. is 100 to 300 kPa, and the storage modulus at 200° C. is 1 to 200 kPa; And / or, the composition has an adhesion of 600 to 3000 g.
6. The composition according to claim 1, characterized in that The dielectric constant of the composition is 2.5-5.
7. A support layer, characterized in that: The support layer comprises a release film layer, a functional layer and a protective film layer in sequence; the functional layer comprises the composition according to any one of claims 1 to 6.
8. The support layer according to claim 7, characterized in that The transmittance of the functional layer is 70 to 100%.
9. The support layer according to claim 7, characterized in that: The haze of the functional layer is 0-10.
10. A display module, characterized in that: The display module includes a display panel and a support layer according to any one of claims 7 to 9 located on a non-light-emitting side of the display panel.